Assessing land use changes and agricultural practices in highland valley-bottom wetlands in Taita Hills, Kenya - Gubamwoyo, S.; Hein, T.; Heiskanen, J.; Kisha, D.G.; Pellikka, P.; Gruber, G.; Omondi, V.A.; Leitner, Sonja; Weigelhofer, G.; Mwamodenyi, J.M.; Obonyo, A.O.; Gettel, G.M. (Elsevier, 2025)
African highlands provide important ecosystem services, supporting >80 million people, with >65 % relying on agriculture in highland valley-bottom wetlands (HVBW). These wetlands have been overlooked in inventories because of their small size, agricultural conversions, management practices, and deforestation. Using remote sensing, interviews, and observations, this study considered the drivers of land use and land cover change in HVBW in Taita Hills, Kenya. We inventoried agricultural and water management practices to understand the impact on ecosystem services and synthesized the information using the DPASER framework (Drivers, Pressures, Actions, State of the ecosystem, Ecosystem services, and Responses). We show that HVBW can be delineated using high-resolution (5 m) Digital Terrain Models (DTM) and the Multiresolution Valley Bottom Flatness (MrVBF) index, and validated with a Normalized Difference Moisture Index (NDMI2) and ground-truthing. HVBW are intensively used by smallholders for cropland and agroforestry. Most conversions occurred more than 50 years ago with the Land Adjudication Act of 1968 but increased from 88 % to 93 % from 1987 to 2023, respectively. Other drivers of wetland degradation include population growth, poverty, climate variation, and food insecurity resulting in more intensive year-round agriculture. To sustain HVBW ecosystem services including carbon storage, biodiversity, and water provisioning, we recommend collaborating with farmers through local organizations to identify and preserve abandoned flooded HVBW as natural systems, and to implement regenerative agriculture in mixed farming systems. Existing policies regarding forests, wetlands, and agricultural management should be harmonized and enforced to promote the use of native and indigenous trees.